New trap for emergent Megaplatypus mutatus - Gatti Liguori, Pablo (2007)
Megaplatypus mutatus (= Platypus mutatus) (Chapuis), an ambrosia beetle (Coleoptera: Platypodidae) native to South America, is a forest pest that attacks live standing trees, affecting commercial poplar and other broadleaf plantations. Traditionally, single-chambered emergence traps have been used to collect live beetles for field and laboratory studies. However, the lack of separation in these chambers results in antagonistic interactions between individuals. Wounded M. mutatus are incapable of successful reproduction and are of little value in physiological and behavioral experiments. We introduce a new, multiple-chambered trap that isolates individual insects until collection, thus increasing the number of uninjured and fully functional insects available for physiological and behavioral experiments.